WAQF AND FINTECH: INTEGRATION METHODS IN DISSEMINATING PRODUCTIVE WAQF ACTIVITIES - Edi, Sarwo; Amalia, Rahmi (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to explain fintech opportunities in socializing waqf in society. This study uses a causal flow of thought in formulating opportunities that occur as a result of the integration of waqf and fintech. This research method is qualitative by using secondary data sources. The main data sources in this research are studies of scientific literature and news media that have good credibility in their editorials. Based on the research results, the use of fintech as a medium for carrying out waqf activities to raise productive funds has a positive effect on waqf socialization in society, especially for the younger generation who are considered active in using fintech platforms in their daily economic life. For the younger generation, integration between waqf services and fintech platforms can provide an opportunity for them to better understand the concept of productive waqf and generate interest in applying it. This research seeks to contribute to fully supporting and motivating productive waqf managers to build digital infrastructure (fintech) in collecting and managing productive waqf funds as well as being a medium of socialization for the public in understanding productive waqf.